Contributions to improve the combined selection of concurrent software testing techniques - Santos, Italo; Furlanetti, Andre B. P.; Melo, Silvana M.; Souza, Paulo Sergio Lopes de; Delamaro, Márcio E.; Souza, Simone R. S. (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST), 2020)
[Context] There are a variety of testing techniques available that present different and often complementary characteristics (e.g., cost of application, effectiveness in revealing defects, types of defects). Considering these complementary characteristics make the selection process even more complex. Testers must make decisions on which techniques they will use in a specific situation. Combining different testing techniques outperforms the use of any single technique alone. [Objective] This paper proposes an approach to support the combined selection of testing techniques for concurrent software projects. The approach is implemented in the SeleCTT-v2 tool, supporting testers to find complementary testing techniques in the body of knowledge proposed in SeleCTT-v1. [Method] We conducted a case study to evaluate the combined selection approach (SeleCTT-v2) with the previous version of the SeleCTT-v1 and to investigate how testers perform a combined selection task for concurrent software projects. [Results and Conclusions] The results indicated a rise in the effectiveness of the combined selection of concurrent testing techniques suggested, which demonstrates SeleCTT-v2 is less likely to make an incorrect recommendation of combined techniques for a concurrent software project, thus avoiding costs associated with the incorrect application of a testing technique. If the testers could access a tool that supports the selection process, the effectiveness of the results would have reached a higher value, as evidenced by our approach. Performing the combination of testing techniques is essential to ensure that software under test has all their features tested to prevent possible errors.